Thermal Degradation Kinetics of Capsaicin on Blanching-Brine-Calcium Pretreatment Red Chili Pepper Drying - Uma Fadzilia Arifin; Mohamad Djaeni (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
Post-harvest red chili pepper (Capsicum frutescens) has highly capsaicin as bioactive compound and moisture content. However, capsaicin is the responsible bioactive compound in chili for hot sensation that easy to degrade by partial oxidation caused introduction of heat in drying process. The objective of this research was to investigate kinetics of capsaicin degradation in the drying process under blanching-brine-calcium pretreatment and various temperatures. For this purposes, chili provided local farmer was pretreated using blanching-brine-calcium pretreatment. Afterward, they were dried at 40, 50, 60, and 70 oC for 8 hours. Degradation of capsaicin content was observed every 2 hours using Thin Layer Chromatography (TLC). Results showed kinetics of capsaicin degradation was categorized as second order reaction. At the same temperature and time, capsaicin retention of blanching-brine-calcium pretreated chili has highest value. The temperature dependence of the capsaicin degradation rate was analyzed using Arrhenius correlation. The activation energy for degradation rate of capsaicin during drying was around 45.10367 kJ/mol.K. It indicated the degradation rate increased as well as increased the temperature at the same time.